Analisis Kemenangan Paket CS’AN pada Pilkada Kota Kupang Tahun 2024: Studi Tentang Penggunaan Influencer Sebagai Strategi Kampanye - Jecson Taniu; Diana S. A. Natalia Tabun; Stefanus Tri Admaja (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This study aims to analyze the winning strategy of Christian Widodo and Serena Francis (CS'AN Package) in the 2024 Kupang City Regional Head Election (Pilkada), focusing on the utilization of social media influencers as a campaign strategy. The method employed is descriptive qualitative, with data collected through observation of digital activities on Instagram and TikTok, campaign content analysis, and in-depth interviews with the campaign team and involved influencers. Grounded in Hafied Cangara's communication effects theory, the effectiveness of the campaign is analyzed through three integrated dimensions: cognitive (building public knowledge and awareness), affective (shaping attitudes and emotional proximity), and conative (triggering concrete actions into voting support). The study concludes that the shift from traditional billboard-based campaigns to influence-based campaigns on social media was the decisive factor for victory in the digital democracy era. The success of the CS'AN Package proves that the credibility of local influencers, when managed with authentic content, can be effectively converted into real electoral votes from the youth voter segment (Generation Z and Millennials).